EVALUATION METHODOLOGY FOR RESEARCH IN ENGINEERING SCIENCES - S. M. Moroz (Высшее образование в России)
This work critically examines the applicability of scientometric indicators (such as H-Index) that are widely used in basic science for evaluation research results in technical sciences. The purpose of this article is to show the specificity of the object and the targets of engineering research. The author strongly argues that it is erroneous to evaluate the effectiveness of a technical researcher according to his publication activity. The paper substantiates the necessity of taking into account the volume of anticipated or already implemented applications of these results for the objective assessment of research and researchers in technical sciences. The number of publications and references has only a subsidiary importance as opposed to the implementation of the results. The author comes to a conclusion that there are no reliable, simple and convenient indices for assessment the research results in technical sciences, and to present day expert evaluation continues to be the most effective tool.